Impact of Production Planning, Inventory Management, and Demand Forecast Accuracy on Operational Performance: The Moderating Role of Sustainability-Oriented Green Supply Chain Management Among Retail Smes in Jakarta - Sudjaniah, Derah; Lu’luatuwwafiroh, Lu’luatuwwafiroh; Utami, Mia; Sugiyono, Sugiyono; Yaqin, Ainul (Ridwan Institute, 2025)
This study examines the influence of production planning, inventory management, and demand forecast accuracy on operational performance, with sustainability-oriented Green Supply Chain Management (GSCM) as a moderating variable, among retail SMEs in Jakarta. Utilizing a mixed methods approach, the research integrates quantitative analysis through Structural Equation Modeling (PLS-SEM) with qualitative insights from semi-structured interviews. The findings reveal that all three operational factors significantly enhance operational performance, supporting theories of aggregate and stochastic production planning, dynamic inventory policies, and real-time demand sensing. Furthermore, GSCM was found to strengthen these relationships, especially when environmental practices were embedded in procurement, logistics, and supplier collaboration. However, the moderating effect varied depending on the firms' readiness and resource capacity to adopt sustainable practices. This research contributes to the existing literature by offering an integrated model tailored for SMEs in developing economies and addressing the limited empirical evidence from Indonesia. It also provides practical guidance for SME practitioners aiming to improve efficiency while aligning with sustainability goals. The study highlights the strategic importance of integrating operational excellence with green supply chain initiatives to build resilience, reduce waste, and enhance long-term competitiveness in dynamic market environments.